English Medium Instruction in Multilingual Context: Exploring Teacher’s Ideology and Practices - Miya, Farmud (Sotang, Yearly Peer Reviewed Journal, 2022)
The present study explores the ideological perspectives of basic level teachers who teach through English medium in EMI classroom. Teachers’ ideology has profound influence on their classroom application. The ideology of a teacher determines the path of teaching-learning pedagogy in the classroom. I have explored the experiences of teachers as an ideological phenomenon. Experiences help to develop one’s ideology. In context of Nepal, teachers are found to use several strategies such as: Paraphrasing, translation, code switching to deliver the classes in EMI classroom. The study is of course qualitative in nature. The sample population consisted of four basic level teachers who have been teaching content subjects like Science, Social, Mathematics and Moral science in English medium. I used purposive non random sampling technique to select the sample population of the study. I employed interview and classroom observation techniques to elicit my data. The interviews were audio recorded with some notes. I analyzed the data qualitatively using the thematic analysis approach. Different codes were formulated to develop themes. The findings gained from the data interpretation showed that teachers used more mother tongue, especially Nepali language to make the text clear to the students in the classroom. Translation, code switching and sometimes paraphrasing were used as teaching pedagogies in a single class. Notably, there were inconsistencies between what the teachers said and what they practiced in their classrooms. It was found that Job market, internationalization and neo-liberalism have fostered in the growth of EMI. Another striking finding was students were found as passive listeners in the classroom. The interaction was rare between the students and teachers. Students were assisted by writing answers of the comprehensive questions. Professional training, sufficient teaching materials and trained teachers need to be focused to make EMI meaningful.